2019
DOI: 10.1002/nvsm.1647
|View full text |Cite
|
Sign up to set email alerts
|

Influence of knowledge, bodily integrity, religion and media on attitudes toward organ donation on the university campus

Abstract: This study examines the influence of knowledge, bodily integrity, religion, and media on attitudes toward organ donation on University campus. A total of 724 participants completed surveys for this study a multivariate regression model was used to test the effects of these factors on participants' attitudes toward organ donation. The variable sets considered are the knowledge of organ donation, bodily integrity, religion, media, and attitudes toward organ donation. The results suggest that the effect of knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The declaration of religiosity was identified as a factor related with negative perception of organ donation. These results are consistent with previous findings, suggesting the effect of the declared religiosity on the probability of making a decision about potential donation, which means that the religious aspect may block donation decisions [13,15,34,[37][38][39][40][41][42] as in other types of donations [12,14,[43][44][45], although there are some studies which deny this [46,47]. However, it is noteworthy that the applied analyses were not completely consistent-LR suggests a suppressing effect of participation in religious practices, whereas CART emphasizes the role of religiosity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The declaration of religiosity was identified as a factor related with negative perception of organ donation. These results are consistent with previous findings, suggesting the effect of the declared religiosity on the probability of making a decision about potential donation, which means that the religious aspect may block donation decisions [13,15,34,[37][38][39][40][41][42] as in other types of donations [12,14,[43][44][45], although there are some studies which deny this [46,47]. However, it is noteworthy that the applied analyses were not completely consistent-LR suggests a suppressing effect of participation in religious practices, whereas CART emphasizes the role of religiosity.…”
Section: Discussionsupporting
confidence: 92%
“…People with a higher level of education seem to be more willing to make decisions about donations. The studies to date have demonstrated that PBMDs are better educated and have a more positive attitude towards science than non-donors [13,15], which seems to be a universal pattern, active irrespective of the cultural circle in which the studies are conducted and the type of donation [12,14,44,[48][49][50][51]. Here, no effect was observed of a higher material status as a predictor of the decision, mentioned by other researchers with respect to, for example, blood donation or a post-mortem donation [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations